1998
DOI: 10.1046/j.1365-2044.1998.00616.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular blocking effects and train‐of‐four fade with cisatracurium: comparison with other nondepolarising relaxants

Abstract: SummaryNeuromuscular blocking drugs exhibit different degrees of fade in response to train-of-four stimulation believed to represent their relative prejunctional effects. The present study was designed to compare the train-of-four fade after cisatracurium and compare this with other commonly used muscle relaxants. Train-of-four fade during onset and recovery of block were recorded after administration of cisatracurium 0.05 or 0.1 mg.kg ¹1 , atracurium 0.5 mg.kg ¹1 , vecuronium 0.08 mg.kg ¹1 , mivacurium 0.15 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 16 publications
(32 reference statements)
1
13
1
1
Order By: Relevance
“…The onset time of the bolus application of 0.1 mg·kg -1 cisatracurium at the adductor pollicis muscle was between three to five minutes, comparable to results in other studies. [7][8][9] The controller performance was regarded as sufficient at an average difference from 2.0% (group D) to 3.2% (group I) between the set point of T1%=10% and the measured degree of neuromuscular blockade. The controller performance for cisatracurium was different from those found for other non-depolarizing muscle relaxants such as vecuronium, 10,11 atracurium 12,13 or rocuronium.…”
Section: Resultsmentioning
confidence: 99%
“…The onset time of the bolus application of 0.1 mg·kg -1 cisatracurium at the adductor pollicis muscle was between three to five minutes, comparable to results in other studies. [7][8][9] The controller performance was regarded as sufficient at an average difference from 2.0% (group D) to 3.2% (group I) between the set point of T1%=10% and the measured degree of neuromuscular blockade. The controller performance for cisatracurium was different from those found for other non-depolarizing muscle relaxants such as vecuronium, 10,11 atracurium 12,13 or rocuronium.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical significance of this prejunctional action is not clear and it has not been correlated with the potency of the drug or the speed of onset of the neuromuscular block [12,13]. Recent studies have found no differences in TOF fade between the more frequently used agents (mivacurium, atracurium, rocuronium, vecuronium and cisatracurium), although there have been previously reported differences between pancuronium and d-tubocurarine [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…The degree of fade in response to TOF stimulation is correlated to the action of the neuromuscular blocking agent on the presynaptic receptor [12,13]. This action induces an inhibition of the positive feedback decreasing transmitter output [14].…”
Section: Discussionmentioning
confidence: 99%
“…First, there are differences in the muscle and monitoring apparatus used to measure neuromuscular responses. In the human study by Carroll et al [16], twitch tensions of the adductor pollicis muscle, which is classified as a slow-twitch muscle, were measured by a mechanomyograph (MMG). In contrast, we studied electromyographic (EMG) responses in the fast-twitch gastrocnemius muscle.…”
Section: Discussionmentioning
confidence: 99%